Invisible and Flexible Printed Sensors Based on ITO Nanoparticle Ink for Security Applications - Gilshtein, Evgeniia; Tacneng, Jasmine; Bolat, Sami; Torres Sevilla, Galo; Romanyuk, Yaroslav E. (Frontiers in Nanotechnology, 2021)
Here, we propose a method to create a transparent security system based on printed conductive indium tin oxide (ITO) - the most widely used transparent conducting oxide material integrated into the devices with high transparency. Commonly used solution-processed ITO annealing methods are utilizing temperatures which are limiting the use of flexible polymeric substrates. Our method combines inkjet printing on flexible temperature-stable colorless polyimide (CPI) substrate with fast flash lamp annealing (FLA). In this study, millisecond pulses of visible light from a xenon lamp induce rapid heating of the ITO films up to 650°C through the light-absorbing additional layer of a colored organic dye onto printed ITO, whereas the CPI bulk never exceeds the melting point. Fabricated flexible ITO patterns on CPI processed with the flash lamp annealing thought the dye layer exhibit a transmittance of up to 85% at the wavelength of 550 nm and sheet resistance of 520 Ω/sq for 70 nm layer thickness. With the proposed technology of our demonstrator realization - transparent glass/window or any other object such as a curved door lock can be used for integrating a touch-enabled transparent security access system, which would be completely invisible.